2020
DOI: 10.1016/j.sjbs.2020.08.015
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial effect of different herbal plant extracts against different microbial population

Abstract: This study evaluates the antimicrobial effects of ethanolic extract of five herbal plants; Guava (Psidium guajava ), Sage ( Salvia officinalis ), Rhamnus ( Ziziphusspina Christi ), Mulberry ( Morusalba L.), and Olive ( Oleaeuropaea L ) leaves against several microbial population representing Gram positive, Gram negative and Mollicutes; S. aureus, E. coli, Pasteurella multocida … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
55
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(61 citation statements)
references
References 40 publications
4
55
0
2
Order By: Relevance
“…However, other studies have reported variable MIC and/or MBC values, which deviated from our results. In the case of E. coli , lower values of MIC and MBC (of 1.25 and 2.5 mg/mL, respectively) were achieved in a 70% ethanolic extract by solid–liquid extraction [ 69 ], while Pereira et al [ 70 ], using water as solvent, found that 1.81 mg/mL of their extract inhibited 25% of microbial growth. Masoko and Makgapeetja [ 71 ], despite finding the same MIC value (2.5 mg/mL) of water extract (solid–liquid extraction) for S. aureus as the MIC of the present study, in the case of ethanolic extracts, the opposite to our results with MAE-Et50, found a very low MIC value (0.26 mg/mL).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, other studies have reported variable MIC and/or MBC values, which deviated from our results. In the case of E. coli , lower values of MIC and MBC (of 1.25 and 2.5 mg/mL, respectively) were achieved in a 70% ethanolic extract by solid–liquid extraction [ 69 ], while Pereira et al [ 70 ], using water as solvent, found that 1.81 mg/mL of their extract inhibited 25% of microbial growth. Masoko and Makgapeetja [ 71 ], despite finding the same MIC value (2.5 mg/mL) of water extract (solid–liquid extraction) for S. aureus as the MIC of the present study, in the case of ethanolic extracts, the opposite to our results with MAE-Et50, found a very low MIC value (0.26 mg/mL).…”
Section: Resultsmentioning
confidence: 99%
“…Masoko and Makgapeetja [ 71 ], despite finding the same MIC value (2.5 mg/mL) of water extract (solid–liquid extraction) for S. aureus as the MIC of the present study, in the case of ethanolic extracts, the opposite to our results with MAE-Et50, found a very low MIC value (0.26 mg/mL). Regarding Salmonella spp., Hemeg et al [ 69 ] tested the antimicrobial activity of olive leaf 70% ethanolic extract by solid–liquid extraction, finding MIC and MBC values of 2.5 and 5 mg/mL, respectively. Techathuvanan et al [ 67 ] found that a commercial olive extract had antimicrobial activity against L. monocytogenes , with a MIC value ranging from 2.2 to 2.6 mg/mL, similar to that observed by Testa et al [ 72 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Além do mais, os extratos de plantas medicinais apresentam diversas atividades farmacológicas, tais como: potencial antibacteriano, antifúngico, antitumoral, antidiabético, anti-inflamatório, dentre outros (Ferraz-filha et al, 2017;Prasathkumar et al, 2021). Diante disso, com essas diversas atividade potenciais o isolamento desses compostos bioativos eficazes e com toxicidade seletiva contra bactérias, a exemplo o S. aureus é recorrente e tem servido como uma alternativa real para os próximos anos (Alvarenga et al, 2016;Hemeg et al, 2020).…”
Section: Introductionunclassified
“…The changes in the structure and chemical composition of compounds found in herbs cause differences in antimicrobial effect of the herbs (Gyawali and Ibrahim, 2014). Antibacterial effects of phytochemicals, secondary metabolites of herbal extracts, and synergistic effects with other antibacterial agents have been reported (Hemeg et al, 2020). This situation led to a worldwide more investigation of herbal extracts as sources of antibacterial agents (Erfan and Marouf, 2019).…”
Section: Introductionmentioning
confidence: 99%